2018
DOI: 10.4149/bll_2018_129
|View full text |Cite
|
Sign up to set email alerts
|

Protection with thymoquinone against formaldehyde-induced neurotoxicity in the rats

Abstract: INTRODUCTION: This study aimed to investigate the neurotoxic damage of formaldehyde (FA), which is commonly used in medicine and industrial fi elds, for the hippocampus of rats and the protective role of thymoquinone (TQ) against this neurotoxicity. METHODS: There were fi ve groups with eight rats in each. Two control groups were formed, in one of them physiological saline was applied and in the other one corn oil was applied. FA was injected in Group 3. Group 4 was exposed to FA and TQ simultaneously. Group 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The MTX group exhibited significant histopathological changes, such as vacuolar alterations, apoptotic cells, and infiltration of inflammatory cells, which have been reported in previous studies (Famurewa et al 2019 ; Shalaby et al 2019 ; Ahmed et al 2021 ; Aslankoc et al 2022 ). However, administration of SP or TQ decreased the neurological lesions, as demonstrated in studies on neurotoxicity induced by lead, nicotine, doxorubicin, and formaldehyde (Khalil et al 2018 ; Saygin et al 2018 ; Galal et al 2019 ; Elsonbaty and Ismail 2020 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The MTX group exhibited significant histopathological changes, such as vacuolar alterations, apoptotic cells, and infiltration of inflammatory cells, which have been reported in previous studies (Famurewa et al 2019 ; Shalaby et al 2019 ; Ahmed et al 2021 ; Aslankoc et al 2022 ). However, administration of SP or TQ decreased the neurological lesions, as demonstrated in studies on neurotoxicity induced by lead, nicotine, doxorubicin, and formaldehyde (Khalil et al 2018 ; Saygin et al 2018 ; Galal et al 2019 ; Elsonbaty and Ismail 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…SP has been shown to have anti-inflammatory properties in previous studies by (Okuyama et al 2017 ), and has been effective against lead-induced neurotoxicity (Khalil et al 2018 ), acrylamide (Bin-Jumah et al 2021 ), and microcystin-LR (Germoush et al 2022 ). TQ has been shown to have anti-inflammatory and antioxidant properties by scavenging ROS and upregulating antioxidants in formaldehyde (Saygin et al 2018 ), microcystin-LR (Abdel-Daim et al 2019 ), acrylamide (Abdel-Daim et al 2020 ), and chlorpyrifos (Aboubakr et al 2021 ) induced toxicity. The oxidative damage and pro-inflammatory cytokines observed in this study could increase the susceptibility of the brain to various neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect was found in this study since α-tocopherol treatment resulted in the highest concentration and sperm motility. Previous studies have shown that FA causes damage because of oxidative stress production, therefore, the use of natural extracts with antioxidant potential can be useful as a treatment, due to its capacity to reduce damage caused by genotoxic agents [39,40]. A study carried out by Bakar et al [41], evaluated the protective effect of proanthocyanidins (PA) compared to vitamin E treatment on FA-induced rat kidney damage.…”
Section: Discussionmentioning
confidence: 99%